Ghost story : a novel of the Dresden files - Butcher, Jim, 1971- (Butcher, Jim, 1971- Dresden files., 2012)
"When an unknown someone shoots him and leaves him to die, Harry Dresden hopes he might be heading to better place. Unfortunately being dead doesn't make Harry's life any easier. Trapped between life and death, he learns that his friends are in serious trouble. Only by finding his murderer can he save them and move on - a feat that would be a lot easier if he had a body and access to his powers."--Back cover.